(untitled) (Veterinary Science, 2021)
Synthetic surfactants have shown positive effects upon the integrity of the cell membrane of cryopreserved sperm without affecting their motility. As pulmonary extracts have surfactant substances, they are expected to produce a positive effect on the boar sperm fertility after cryopreservation. In order to have preliminary evidence regarding the absence / presence of toxicity of pulmonary extracts on semen, ejaculates from two boars, aged between 24 and 30 months, were used. Each ejaculate was divided into two groups. One of them was diluted with a middle-term commercial medium (Control group) and the other with the same medium plus the addition of: 2.5, 5 or 10% of pig pulmonary extract (Treatment group). As indicators of the treatment effect on semen quality, the live-dead ratio, the host test and the acrosome integrity were determined. Samples were evaluated after 0, 24 and 48 hours of incubation at 17 ° C and 36 ° C. The experiment was repeated in three ejaculates of each one of the boars, in order to determine interaction between the components of the preservation medium and the pulmonary extracts, and the quality of the porcine sperm. The results show that there are no differences in the parameters observed between the different evaluation moments, nor in the different extract variations, as well as no difference between individuals. It is concluded that pulmonary extracts do not present toxic effects on porcine sperm.